Two cases of possible neuro-Sweet disease with meningoencephalitis as the initial manifestation - Go Makimoto; Yasuhiro Manabe; Chizuru Yamakawa; Daiki Fujii; Yasuko Ikeda-Sakai; Hisashi Narai; Nobuhiko Omori; Koji Abe (Neurology International, 2012)
We report 2 cases that were considered to be neuro-Sweet disease. They initially manifested with meningoencephalitis and no skin lesions, and rapidly improved with corticosteroid therapy. In both cases, patients complained of meningitic symptoms such as fever and headache, and HLA-B54 and -Cw1 turned out to be positive over the clinical course. Cerebrospinal fluid analysis showed increased levels of lymphocytes and protein. In case #1, fluid-attenuated inversion recovery (FLAIR), magnetic resonance imaging (MRI) and diffusion-weighted images (DWI) showed high-intensity signals in the right dorsal medulla oblongata, bilateral dorsal midbrain, and left thalamus. In case #2, FLAIR and DWI showed high-intensity signals in the bilateral cerebellar cortex and left caudate nucleus. Symptoms and MRI images were markedly improved in both cases after corticosteroid pulse therapy. According to published diagnostic criteria, these 2 cases were considered possible neuro-Sweet disease. These cases suggest that the combination of meningoencephalitis and HLA specificity is important to consider the possibility of neuro-Sweet disease, even without skin lesions.